Dramatic change in viscosities of pure ionic liquids upon addition of molecular solvents - Khupse, Nageshwar D.; Kumar, Anil (Journal of Solution Chemistry, 2009)
Viscosities of binary mixtures of pyridinium based ionic liquids (1-butyl pyridinium tetrafluoroborate, [BP][BF(4)], 1-butyl 3-methyl pyridinium tetrafluoroborate [3-MBP][BF(4)], 1-butyl 4-methyl pyridinium tetrafluoroborate, [4-MBP][BF(4)]), and phosphonium based ionic liquids, (tetrabutyl phosphonium alaninate, [TBP][Ala]; tetrabutyl phosphonium valinate, [TBP][Val]) with the molecular solvents, water, methanol and dichloromethane, have been measured at 298.15 K. A Brookfield ultra-rheometer was employed to measure the reported viscosities. The drop in viscosity in the close vicinity of pure ionic liquid is more prominent in polar solvents like water compared to less polar solvents. The temperature dependence of this observation was also studied for binary mixtures of [4-MBP][BF(4)] with water in range of 298.15-323.15 K. The Vogel-Fulcher-Tamman (VFT) equation was employed to investigate the temperature dependence of the viscosities of pure pyridinium-based ionic liquids in the temperature range from 298.15-323.15 K.
Keywords: ionic liquids; Molecular solvents; VFT equations; viscosity

Delineating solute-solvent interactions in binary mixtures of ionic liquids in molecular solvents and preferential solvation approach - Khupse, Nageshwar D.; Kumar, Anil (Journal of Physical Chemistry B, 2011)
The effect of solute-solvent and solvent-solvent interactions on the preferential solvation of solvatochromic indicators in binary mixtures of ionic liquids with molecular solvents has been investigated. The binary mixtures of the pyridinium-based ionic liquids 1-butylpyridinium tetrafluoroborate ([BP][BF4]), 1-butyl-3-methylpyridinium tetrafluoroborate ([3-MBP][BF4]), and 1-butyl-4-methylpyridinium tetrafluoroborate ([4-MBP][BF4]) with molecular solvents like water, methanol, and dichloromethane have been selected for this investigation. The effect of addition of ionic liquids to molecular solvents on the polarity parameters E-T(N), Kamlet-Taft parameters, hydrogen bond donor ability (HBD) (alpha), hydrogen bond acceptor ability (HBA) (beta), and polarizability (pi*) was obtained. The polarity parameters of the mixture display nonideality on addition of ionic liquids to water and dichloromethane. On the other hand, strong synergetic effects were seen in the ionic liquid-methanol binary mixtures. The preferential solvation models have been employed to analyze the collected data in order to achieve information on solute-solvent interactions in these binary mixtures.

Do anions influence the polarity of protic ionic liquids? - Shukla, Shashi Kant; Khupse, Nageshwar D.; Kumar, Anil (Physical Chemistry Chemical Physics, 2012)
Polarity studies in two classes of imidazolium-based protic ionic liquids (PILs) possessing [HSO4](-), [HCOO](-),[CH3COO](-) and [CH3CH2COO](-) anions were carried out using a solvatochromic method from 298.15 to 353.15 K. For 1-methylimidazolium class of PILs, ET(30) was found to be independent over the entire range of temperature, while ET(30) was noted to decrease with a rise in temperature in the case of 1-butylimidazolium class of PILs containing [CH3COO](-) and [CH3CH2COO](-) anions. The ET(30) value decreases in both the classes upon varying the anions ([HSO4](-), [HCOO](-), [CH3COO](-) and [CH3CH2COO](-)). The E-T(30) value is controlled by hydrogen bond acceptor basicity, b, and dipolarity/polarizability, pi*. The E-T(30) value for PILs varies inversely to the strength of the coulombic interaction between ions in PILs. Strong interactions between ions lead to lower E-T(30) values. Unlike the poor thermal effect on E-T(30), the Kamlet-Taft parameters i.e. alpha, beta and pi* have pronounced thermal effect in the imidazolium-based PILs. Variation in the Kamlet-Taft parameters is controlled by the stabilization of ions and the degree of proton transfer from Bronsted acid to Bronsted base.